1989
DOI: 10.1139/v89-202
|View full text |Cite
|
Sign up to set email alerts
|

Étude structurale de la liaison thioamide: Synthèse et conformation de dérivés de la thioalanine et de la thioglycine

Abstract: Requ le 15 juin 1 9 8 8~ ANDRE G. MICHEL, CHAKIB AMEZIANE-HASSANI, GASTON BOULAY et GILLES LAJOIE. Can. J. Chem. 67, 1312 (1989). Cette Ctude rapporte la synthkse, la dktermination de structures cristallines et l'analyse conformationnelle par calculs empiriques de la N-tertiobutyloxycarbonyl N'-mCthylthioalanine (Boc-Alas-NHCH3, C9H18N202S) et de la N-tertiobutyloxycarbonyl N'-mCthylthioglycine (Boc-GlyS-NHCH3, C8H16N2O2S), C O~P O S C S a l'intcrieur desquels la liaison amide conventionnelle a CtC remplacCe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The ψ[CSNH]Aib homo‐polymer folds in a semi ‐extended helical conformation with the CS pointing away and NH pointing toward the helix axis and both perpendicular to it. The mono‐ and dithionated Ac‐ (or Boc)‐Xxx‐NHMe (XxxGly and l ‐Ala) were investigated also by Lajoie and coworkers . In general, it was found that the energy maps do not vary significantly from those of the related oxo‐derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The ψ[CSNH]Aib homo‐polymer folds in a semi ‐extended helical conformation with the CS pointing away and NH pointing toward the helix axis and both perpendicular to it. The mono‐ and dithionated Ac‐ (or Boc)‐Xxx‐NHMe (XxxGly and l ‐Ala) were investigated also by Lajoie and coworkers . In general, it was found that the energy maps do not vary significantly from those of the related oxo‐derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The dots on some maps are the (ϕ,ψ) values found in experimental X‐ray crystal data. Dot 1: Boc‐Glyt‐Ala‐Aib‐OMe,71 Dot 2: (Z)‐Glyt‐Glyt‐Gly‐OBzl,73 Dot 3: (Z)‐Glyt‐Gly‐OBzl,74 and Dot 4: Boc‐Glyt‐NHMe 3…”
Section: Resultsmentioning
confidence: 99%
“…One therapeutic problem that arises when using peptides is the rapid degradation by the peptidases that normally digest dietary proteins. Noncoding amino acids can confer resistance to such enzymatic degradation 2–4. Noncoded amino acids have also been useful for probing the function of protein structural motif,5–7 during the process of de novo design,8–13 to build structures with novel folds or particular secondary structures14, 15 or for creating new combinatorial chemistry libraries 16–21.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations